1999
DOI: 10.1002/(sici)1096-9896(199905)188:1<56::aid-path304>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2 (MMP-2) immunoreactive protein?a new prognostic marker in uveal melanoma?

Abstract: Uveal melanoma is the most common primary intraocular tumour. Once haematogenous metastasis has occurred, there is no cure for the disease and there is an obvious need for new biological prognostic markers to estimate the risk of metastasis. In this study, the expression of matrix metalloproteinase‐2 (MMP‐2) was characterized immunohistochemically in 29 human uveal melanomas. Enzyme‐linked immunoassays and gelatin zymographies were assessed in order to quantify the expression of gelatinases A and B, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…In the present study, we compared secretion of MMP-2 and MMP-9 with invasiveness and other prognostic indicators. No correlation was found between secretion of either MMP and invasiveness, although recent evidence has suggested that MMP-2 is correlated with indicators of poor prognosis in uveal melanoma 33. One explanation for the lack of correlation is that MMP-2 and MMP-9 degrade mainly type IV collagenase and gelatin, and fibronectin was used as a barrier to invasion in this study, as previous investigations had established fibronectin as the preferred substrate for uveal melanoma cell attachment 34.…”
Section: Discussionmentioning
confidence: 59%
“…In the present study, we compared secretion of MMP-2 and MMP-9 with invasiveness and other prognostic indicators. No correlation was found between secretion of either MMP and invasiveness, although recent evidence has suggested that MMP-2 is correlated with indicators of poor prognosis in uveal melanoma 33. One explanation for the lack of correlation is that MMP-2 and MMP-9 degrade mainly type IV collagenase and gelatin, and fibronectin was used as a barrier to invasion in this study, as previous investigations had established fibronectin as the preferred substrate for uveal melanoma cell attachment 34.…”
Section: Discussionmentioning
confidence: 59%
“…Ten individuals (men/women: 8/2) with spinal cord injury [level: C6 to T6; years since injury: 12.5 (2-23) years (mean and range); age: 35 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) years; mean weight: 78 ± 3.8 (SE) kg] participated in the present study, which was approved by the Municipal Ethical Committee of Copenhagen. Six were tetraplegic and four were paraplegic.…”
Section: Methodsmentioning
confidence: 99%
“…ELISAs were performed on 96well microtiter plates using standard protocols as described elsewhere. 45 Briefly, a 96-well microtiter plate (Nunc Maxisorb; Nalge Nunc International, Roskilde, Denmark) was coated with a specific monoclonal antibody against the analyte. A polyclonal antibody produced in chicken against the ana-lyte was used as a secondary antibody.…”
Section: Sample Preparations For Biochemical Analysismentioning
confidence: 99%
“…Evidence has recently emerged that MMP-2 may be a prognostic marker in uveal melanoma. An immunohistochemical study of 29 uveal melanomas by Vaisanen and colleagues demonstrated that positive immunostaining for MMP-2 in tumour cells correlated significantly with poorer 5 year relapse free and overall survival rates and a higher incidence of visceral metastases 122. Levels of MMP-2, TIMP-1, and TIMP-2 in the vitreous, where available for analysis, were not elevated compared with controls, and had no prognostic significance.…”
Section: Mmps and Timps In Vitreoretinal Diseasesmentioning
confidence: 99%